Prenatal diagnosis and molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome derived from ring chromosome 2 - Chih-Ping Chen; Ming Chen; Schu-Rern Chern; Peih-Shan Wu; Shun-Ping Chang; Dong-Jay Lee; Yu-Ting Chen; Li-Feng Chen; Jun-Wei Su; Alan Hwa-Ruey Hsieh; Alex Hwa-Jiun Hsieh; Wayseen Wang (Elsevier, 2012)
Objective: To present prenatal diagnosis and molecular cytogenetic characterization of mosaicism for a small supernumerary marker chromosome (sSMC) derived from ring chromosome 2 [r(2)]. Methods and Results: A 35-year-old woman underwent amniocentesis at 17 weeks of gestation, because of advanced maternal age. Amniocentesis revealed a de novo ring-shaped sSMC in 11 of 23 colonies of cultured amniocytes. Repeated amniocenteses were made. The sSMC was characterized by array comparative genomic hybridization (aCGH), interphase fluorescence in situ hybridization (FISH) and quantitative fluorescent polymerase chain reaction (QF-PCR) on uncultured amniocytes. In uncultured amniocytes, aCGH showed a 39.49-Mb genomic gain in chromosome 2 encompassing 2q11.2→q21.2, interphase FISH revealed a mosaic level of 52% (52/100 cells), and QF-PCR manifested a diallelic pattern for chromosome 2, with gene dosage increase in the paternal allele of proximal 2q-specific DNA markers. In cultured amniocytes, the sSMC was characterized by metaphase FISH, spectral karyotyping (SKY) and multicolor banding (MCB) to contain the centromere and proximal 2q, and the karyotype was 47,XX,+r(2)(p11.1q21.2)[14]/46,XX[11]. The pregnancy was terminated. The fetus postnatally manifested facial dysmorphisms. Postnatal cytogenetic analyses revealed the karyotypes of 47,XX,+r(2)[12]/46,XX[28] in cord blood, 47,XX,+r(2)[7]/46,XX[33] in umbilical cord, 47,XX,+r(2)[13]/47,XX,+idic r(2)[3]/46,XX[24] in placenta and 47,XX,+r(2)[8]/47,XX,+idic r(2)[1]/46,XX[31] in amnion. Conclusion: Molecular cytogenetic techniques such as aCGH, interphase FISH and QF-PCR on uncultured amniocytes, and SKY, MCB and metaphase FISH on cultured amniocytes are useful for characterization of the nature of a prenatally detected sSMC.